A thymosin beta-4 is involved in production of hemocytes and immune defense of Hong Kong oyster, Crassostrea hongkongensis. (April 2016) - Li, Jun; Zhang, Yuehuan; Liu, Ying; Zhang, Yang; Xiang, Zhiming; Qu, Fufa; Yu, Ziniu
Abstract: Thymosin beta-4 (Tβ4) is a ubiquitous protein with multiple and diverse intracellular and extracellular functions in vertebrates. In this study, the full-length cDNA of Tβ4 was cloned and identified in Crassostrea hongkongensis, designated as ChTβ4 . The full-length cDNA of ChTβ4 consists of 530 bp with an open reading frame of 126 bp encoding a 41 amino acid polypeptide. SMART analysis indicated that there is one thymosin domain and a highly conserved actin-binding motif (18LKKTET23) in ChTβ4. In vivo injection of recombinant ChTβ4 protein could significantly increase total hemocytes count in oysters, and knockdown of the expression of ChTβ4 resulted in a significant decrease in the circulating hemocytes. Tissue distribution analysis revealed a ubiquitous presence of ChTβ4, with the highest expression in hemocytes. The upregulated transcripts of ChTβ4 in response to bacterial challenge and tissue injury suggest that ChTβ4 is involved in both innate immunity against pathogen infection and wound healing. Moreover, bacteria-clearance experiment showed ChTβ4 could facilitate the clearance of injected bacteria in oysters. In vivo injection with ChTβ4 resulted in reduction of the intracellular ROS in hemocytes, which was associated with increased expression of antioxidant enzymes Cu/Zn superoxide dismutase (SOD), Catalase, and Glutathione Peroxidase (GPX) by pre-treatment with ChTβ4. These results suggest that ChTβ4 is a thymosin beta-4 homolog and plays a vital role in the immune defense of C. hongkongensis . Highlights: ChTβ4 stimulated an increase in circulating hemocytes. ChTβ4 is involved in both bacterial challenge and wound healing. ChTβ4 facilitates the clearance of Vibrio alginolyticus . ChTβ4 inhibits intracellular ROS production and upregulates the expression of antioxidant enzymes in the oyster.